Degenerative Encephalopathy in Nova Scotia Duck Tolling Retrievers Presenting with a Rapid Eye Movement Sleep Behavior Disorder. (22nd September 2016) - Barker, E.N.; Dawson, L.J.; Rose, J.H.; Van Meervenne, S.; Frykman, O.; Rohdin, C.; Leijon, A.; Soerensen, K.E.; Järnegren, J.; Johnson, G.C.; O'Brien, D.P.; Granger, N.
Abstract : Background: Neurodegenerative diseases are a heterogeneous group of disorders characterized by loss of neurons and are commonly associated with a genetic mutation. Hypothesis/Objectives: To characterize the clinical and histopathological features of a novel degenerative neurological disease affecting the brain of young adult Nova Scotia Duck Tolling Retrievers (NSDTRs). Animals: Nine, young adult, related NSDTRs were evaluated for neurological dysfunction and rapid eye movement sleep behavior disorder. Methods: Case series review. Results: Clinical signs of neurological dysfunction began between 2 months and 5 years of age and were progressive in nature. They were characterized by episodes of marked movements during sleep, increased anxiety, noise phobia, and gait abnormalities. Magnetic resonance imaging documented symmetrical, progressively increasing, T2‐weighted image intensity, predominantly within the caudate nuclei, consistent with necrosis secondary to gray matter degeneration. Abnormalities were not detected on clinicopathological analysis of blood and cerebrospinal fluid, infectious disease screening or urine metabolite screening in most cases. Postmortem examination of brain tissue identified symmetrical malacia of the caudate nuclei and axonal dystrophy within the brainstem and spinal cord. Genealogical analysis supports an autosomal recessive mode of inheritance. Conclusions and Clinical Importance: A degenerative encephalopathy was identified in young adult NSDTRs consistent with a hereditary disease. The prognosis is guarded due to the progressive nature of the disease, which is minimally responsive to empirical treatment.